Impact of policy changes on technical efficiency on farmaers: empirical evidence from Nigerian small scale food crop farmers (2008)
The study quantitatively determine the impact of policy changes on technical efficiency of small scale food crop farmers in Ondo State, Nigeria, using the stochastic frontier methodology. Given the specifications of the Cobb-Douglas stochastic models, the result shows that the elasticity of mean value of farm output is an increasing function of land, labour and implementation. The mean value of output is also estimated to be an increasing function of agrochemicals and seeds. The results indicated that an increasing returns-to scale exists among the farmers. The analysis shows a wide variation in the estimated technical efficiencies ranging between 0.22 and 0.89. The result of stimulation on policy variation shows thatthe level of technical efficiency would significantly increase with rising level of education, farming experience and amount of credit used and decline with the age of the farmers.